2004
DOI: 10.1074/jbc.m401045200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Apo Forms of ψ 55 tRNA Pseudouridine Synthase from Mycobacterium tuberculosis

Abstract: The three-dimensional structure of the RNA-modifying enzyme, ⌿55 tRNA pseudouridine synthase from Mycobacterium tuberculosis, is reported. The 1.9-Å resolution crystal structure reveals the enzyme, free of substrate, in two distinct conformations. The structure depicts an interesting mode of protein flexibility involving a hinged bending in the central ␤-sheet of the catalytic module. Key parts of the active site cleft are also found to be disordered in the substrate-free form of the enzyme. The hinge bending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…The shorter thumb loop in Cbf5 largely is disordered in the H/ACA RNP (30) (Fig. 5C), as is the case for apoTruB (35,42) as well as Cbf5-Nop10 (27-29). It has been proposed that this loop would become ordered when substrate binds, interacting with the major groove of PS1 (30), as illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The shorter thumb loop in Cbf5 largely is disordered in the H/ACA RNP (30) (Fig. 5C), as is the case for apoTruB (35,42) as well as Cbf5-Nop10 (27-29). It has been proposed that this loop would become ordered when substrate binds, interacting with the major groove of PS1 (30), as illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Crystal structures of representative members of each family have been determined and reveal that even though sequence conservation between any two sub-families is low, all Ψ synthases have a structurally conserved catalytic core. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The only structures of Ψ synthasesubstrate complexes published to date are those of TruB and RluA co-crystallized with small RNA stem-loops that are minimal substrates of the enzymes. 21,22,26,27 These structures show that the substrate RNA binds to a positively charged surface on the protein with the target base flipped out of the stem-loop and into an active site cleft next to an invariant catalytic Asp.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of Y173, it has been suggested that, at least in TruB, the corresponding tyrosine (Y67 in E. coli TruB) is involved in maintaining the catalytic aspartate in the charged state through the maintenance of a salt bridge (Hoang and Ferré-D'Amaré 2001;Chaudhuri et al 2004). Our results with mutations at this position suggest that a tyrosine at this position is indeed critical, but there was detectable activity with all the mutants except Y173S.…”
Section: Comparison Of Trua and Pus1pmentioning
confidence: 99%